The Future of Asian & Pacific Cities Transformative Pathways Towards Sustainable Urban Development. - Thailand United Nations (2019)
The cities of 2030, 2050 and 2100 will be very different from today. They will be cities transformed in their demographic composition, in their implementation of technology and in their wider ecological contexts. The challenges of building cities sustainable enough to meet the chang ing needs of the future will require new ways of thinking and working, as well as new kinds of multi-stakeholder initiatives and partnerships. The Future of Asian and Pacific Cities report 2019 makes the case for four priorities and four approaches to realize a sustainable urban future in Asia and the Pacific. A sustainable future occurs when urban and territorial planning lays a foundation; resilience guards against future risk; smart cities deploy the best technology for the job; and financing tools help pay for it all. Getting these essentials right in Asian and Pacific cities today is vital in order to adapt to the demands of tomorrow and to deliver on the 2030 Agenda for Sustainable Development and the New Urban Agenda.

Source: Publisher
Includes references.
Keywords: Sustainable urban development; Sustainable urban development -- Asia; Sustainable urban development -- Pacific; City planning; Sustainable development